2009
DOI: 10.4062/biomolther.2009.17.4.395
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Insulin on Hydrogen Peroxide-Induced Oxidative Stress in C6 Glial Cells

Abstract: -Insulin appears to play a role in brain physiology, and disturbances of cerebral insulin signalling and glucose homeostasis are implicated in brain pathology. The objective of the present study was to investigate the protective effects of insulin under conditions of oxidative stress induced by hydrogen peroxide (H2O2) in C6 glial cells. Insulin at concentration of 10 −7 M could prevent 12 h H2O2-induced cell death. The formation of reactive oxygen species (ROS), nitric oxide (NO) and 2-thiobarbituric acid-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Therefore, we hypothesized that the protective mechanism of PF on C6 glial cells against H 2 O 2 -induced oxidative damage may be due to its up-regulation of cellular antioxidant system, such as SOD activity, that is capable of scavenging ROS. Li et al [35] reported that PF treatment inhibited production of free radicals by enhancement of SOD activity and reduction of malondialdehyde contents in the brain [36]. In agreement with previous result, our finding showed that treatment of the cells with PF enhanced SOD activity compared to H 2 O 2 -treated control group.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we hypothesized that the protective mechanism of PF on C6 glial cells against H 2 O 2 -induced oxidative damage may be due to its up-regulation of cellular antioxidant system, such as SOD activity, that is capable of scavenging ROS. Li et al [35] reported that PF treatment inhibited production of free radicals by enhancement of SOD activity and reduction of malondialdehyde contents in the brain [36]. In agreement with previous result, our finding showed that treatment of the cells with PF enhanced SOD activity compared to H 2 O 2 -treated control group.…”
Section: Discussionsupporting
confidence: 92%
“…Akt is an initiator of the downstream pathways that inhibit the apoptotic pathways (Chan 2004). Akt also exerts a strong influence on survival of neurons by inhibiting proteins that mediate apoptosis (Kim and Han 2005;Mahesh and Kim 2009). Ras can directly activate PI3-K, an upstream effector for activation of Akt (Chan 2004).…”
Section: Protein Kinase B (Pkb; Akt)mentioning
confidence: 99%
“…After each specific treatment, the cells were treated with MTT solution (1/10 volume of culture medium) and incubated in a 5% CO 2 incubator at 37 • C for 1 h. The absorbance for each reaction product was measured with an ELISA reader (Bio-Rad, Germany) at a wavelength of 450 nm. The results are expressed as the percentage of MTT reduction, with the assumption that the absorbance of the control cells is 100% (Mahesh and Kim, 2009). …”
Section: Determination Of Cell Viabilitymentioning
confidence: 99%